Extractive Metallurgy of Nickel, Cobalt and Platinum-Group Metals - Crundwell, Frank K.; Moats, Michael S.; Ramachandran, Venkoba; Robinson, Timothy G.; Davenport, William G. (Elsevier, 2011)
This book describes and explains the methods by which three related ores and recyclables are made into high purity metals and chemicals, for materials processing. It focuses on present day processes and future developments rather than historical processes. Nickel, cobalt and platinum group metals are key elements for materials processing. They occur together in one book because they (i) map together on the periodic table (ii) occur together in many ores and (iii) are natural partners for further materials processing and materials manufacturing. They all are, for example, important catalysts with platinum group metals being especially important for reducing car and truck emissions. Stainless steels and CoNiFe airplane engine super alloys are examples of practical usage. The book emphasizes a sequential, building-block approach to the subject gained through the author’s previous writings and extensive experience. Due to the multiple metals involved and because each metal originates in several types of ore, e.g. tropical ores and arctic ores, this necessitates a multi-contributor work drawing from multiple networks and both engineering and science.